Education on human rights values in Moroccan school; Philosophy textbooks as a study case - Douz, Abdelilah (Journal of Educational and Psychological Sciences, 2022)
The study aims at highlighting the status occupied by problematic based education on human rights values in Moroccan education system through the present courses of philosophy in secondary school. This problematic is concerned as an interest that imposed itself in the societal changes since the beginning of the third decade. In the light of this, the study endeavers the ways to reinforce human rights in Moroccan schools. Thus, refers to the importance and the centrality of values within the components of the education system, in addition to its cruciality in the development of learning pattern.As well, the importance of the topic comes as a societal affair which aims at socioliziting generations to share the national commons on human rights values and the consolidation of civic behaviors.So, the question of the best key to tackle values education have been a dispute between various actors in the society. Hence, this issue has made a public debate to pave the way for new strategy platform to reform the education system. Thus, integrating human rights education into educational system refers to the educational philosophy based on and the societal project from which we derive the major goals. This study based on the analytic descriptive method using Content analysis technique in reading and analysing ideological and cultural patterns which lead to many results, to say but few, though, The presence of human rights values in text books. But the strategy to teach human rights values does not manifest itself, and shows no clear principles and values. However, the study proposes some recommendations as the necessity of teaching human right in learning programms as an independent subject with identified objectives.
Keywords: Education; Values; Human rights; competencies